The Name You Once Gave Me - Phillips M. Mike (Quick reads)
Daniel grew up without a father. His mother told him that his father died the year he was born, and he had no reason to doubt her until now! With his wedding only weeks away, Daniel is thinking only about the future. Until a chance meeting has him looking into his past. When an old man tells him that he ran into his father recently, it comes as a shock to Daniel. Hed always believed that his father died when was a baby. Daniels mother says the old man is mistaken, and at first he believes her. But he changes his mind when he finds a photo album hidden amongst the junk in the garden shed. In the album are pictures of his mother with a strange man, holding a baby. Without telling his mother, Daniel sets out to find his father. One by one, he tracks down his mothers old friends. After a few false starts, he is certain that he has found his father. They arrange to meet, and both are surprised by the affection they feel for each other. Daniel invites his father to the wedding, but he waits until the night before to tell his mother. It is only then that he finds out the truth!